Bullying from the Perspective of Educational Foundations in Indonesia: Philosophical, Psychological, Sociological, and Legal Analysis - Nur Aini, Fitria; Pramono, Harry (Jurnal Multidisiplin Indonesia, 2025)
Bullying remains one of the most prevalent forms of violence experienced by students in Indonesian educational settings. Manifesting through physical, verbal, and psychological aggression, bullying not only disrupts students' sense of safety but also violates children's fundamental rights to protection, well-being, and equitable access to education. National educational data reveal a consistently increasing trend in bullying cases across levels, indicating that the problem is systemic rather than incidental. This study aims to analyze bullying through the lens of Indonesia's educational foundations—philosophical, psychological, sociological, and juridical—using a literature-based research design. The findings show that bullying contradicts the philosophical values of Pancasila and highlights gaps in character education implementation. Psychologically, the issue is linked to students' moral development stages and the limited availability of emotional literacy and counseling services in schools. From a sociological standpoint, bullying is reinforced by school culture, peer-group dynamics, and broader social influences, including digital media. Juridically, although Indonesia has comprehensive regulations protecting children, the implementation remains weak due to inadequate reporting systems, SOPs, and enforcement mechanisms in schools. The study concludes that despite strong educational foundations, bullying persists due to cultural, structural, and systemic deficiencies. Strengthening preventive systems, enhancing teacher capacity, improving parental involvement, and enforcing existing regulations are essential steps toward creating a safer educational environment for all students.